Pelaksanaan Diversi dalam Penyelesaian Perkara Pidana Anak pada Cabang Kejaksaan Negeri Tanjung Jabung Timur di Nipah Panjang, Provinsi Jambi - Disfany Aprillia Putri; Agus Ariadi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
This study aims to find out the procedure for handling diversion of child criminal cases and the application of diversion in practice along with the obstacles that are obstacles in its implementation. The research uses a mixed legal approach, namely normative and empirical with an analytical descriptive method. Data was obtained through literature studies of laws and regulations, books, and legal journals, as well as field data through observation and interviews with law enforcement officials, community supervisors, and community leaders in the East Tanjung Jabung District Attorney's Branch Area in Nipah Panjang, Jambi Province. The data obtained was analyzed qualitatively. The results of the study show that the procedure for implementing diversion has been carried out in accordance with the provisions of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System through deliberations involving perpetrators, victims, families, community leaders, and law enforcement officials. However, in practice, the implementation of diversion has not been running optimally because it is still influenced by the rejection of victims, low public understanding of diversion, limited mediation capabilities of law enforcement officials, and limited facilities of support and community guidance. This study concludes that the implementation of diversion has been carried out in accordance with the provisions of the law, but there are still structural and cultural obstacles that affect the effectiveness of its implementation, so it is necessary to increase the capacity of law enforcement officials, strengthen socialization to the community, and optimize the role of child assistance institutions so that